A comparison of all-in-one and conventional sorghum silage with and without MGA for feedlot heifers - Smart, L.I.; Drake, C.L. (Kansas State University. Agricultural Experiment Station, 2011)
Silage is being utilized in larger quantities in beef cattle growing and fattening rations. Hammes et al. (1964) showed that higher levels of corn silage can be used because gains from high silage and high grain rations are similar. However, more total digestible nutrients may be harvested per acre and the cost of gain is usually less with silage. Several investigators have shown advantages to certain additives with silage.
Keywords: Beef; Sorghum silage; MGA; Feedlot heifers